High-resolution VLA observations of FR0 radio galaxies: the properties and nature of compact radio sources. Issue 2 (13th November 2018) - Baldi, Ranieri D; Capetti, Alessandro; Giovannini, Gabriele
Abstract: We present the results of Karl G. Jansky Very Large Array (VLA) observations regarding the properties of FR0 radio galaxies, the compact radio sources associated with early-type galaxies that represent the bulk of the local radio-loud population of active galactic nuclei. We obtained A-array observations at 1.5, 4.5 and 7.5 GHz for 18 FR0s from the FR0 CAT sample: these are sources atz < 0.05, which are unresolved in the FIRST images and spectroscopically classified as low-excitation galaxies (LEGs). Although we reach an angular resolution of ∼0.3 arcsec, the majority of the 18 FR0s are still unresolved. Only four objects show extended emission. Six have steep radio spectra, 11 have flat cores, while one shows an inverted spectrum. We find that (i) the ratio between the core and total emission in FR0s is ∼30 times higher than that in FRIs, and (ii) FR0s have the same properties as FRIs from the nuclear and host points of view. FR0s differ from FRIs only in the paucity of extended radio emission. Various evolutionary scenarios were investigated: (i) the possibility that all FR0s are young sources eventually evolving into extended sources was ruled out by the distribution of radio sizes; (ii) similarly, a time-dependent scenario, in which a variation of accretion or jet launching prevents the formation of large-scale radio structures, appears to be implausible owing to the large abundance of subkiloparsec objects; (iii) a scenario in which FR0s are produced by mildly relativistic jets is consistent with the data but requires observations of a larger sample if it is to be properly tested.